Syndicated loans and CDS positioning - I\~naki Aldasoro; Andreas Barth (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2017)
This paper analyzes banks' usage of CDS. Combining bank-firm syndicated loan data with a unique EU-wide dataset on bilateral CDS positions, we find that stronger banks in terms of capital, funding and profitability tend to hedge more. We find no evidence of banks using the CDS market for capital relief. Banks are more likely to hedge exposures to relatively riskier borrowers and less likely to sell CDS protection on domestic firms. Lead arrangers tend to buy more protection, potentially exacerbating asymmetric information problems. Dealer banks seem insensitive to firm risk, and hedge more than non-dealers when they are more profitable. These results allow for a better understanding of banks' credit risk management.
Keywords: G21; G28; 330; syndicated loans; CDS; speculation; capital regulation; EMIR; cross-border lending; asymmetric information